COMPETENT APPROACH IN THE EDUCATIONAL PROCESS - Khudoyberdiyeva Nilufar Bozorovna (Journal Park Publishing, 2023)
This article analyzes the term competence, its origin and importance in the educational process. Also, are given comments on the scientific research of foreign researchers regarding competence.
Keywords: competence, education, training, research, methods, methodology, teaching.